Concomitant occurrence of primary hyperparathyroidism (PHPT) due to mediastinal parathyroid adenoma and sublingual thyroid gland: the role of parathyroid technetium‐99m‐MIBI scintigraphy. Issue 11 (5th October 2017) - Choukry, Sara; Benouhoud, Jaafar; Cherkaoui Salhi, Ghofrane; Taleb, Sara; Guensi, Amal; Choukry, Karim
Key Clinical Message: The concomitant appearance of a sublingual thyroid and primary hyperparathyroidism due to parathyroid mediastinal adenoma is not common. This co‐occurrence can lead to a misdiagnosis by morphological imaging methods alone. This case emphasizes the role of 99mTc‐MIBI scintigraphy in the detection of parathyroid ectopic adenoma in a patient with an ectopic thyroid gland. This more accurate location of parathyroid scintigraphy is of great benefit to the surgeon for surgical excision. Abstract : The concomitant appearance of a sublingual thyroid and primary hyperparathyroidism due to parathyroid mediastinal adenoma is not common. This co‐occurrence can lead to a misdiagnosis by morphological imaging methods alone. This case emphasizes the role of 99mTc‐MIBI scintigraphy in the detection of parathyroid ectopic adenoma in a patient with an ectopic thyroid gland. This more accurate location of parathyroid scintigraphy is of great benefit to the surgeon for surgical excision.